Manufacturing civil society: principles, practices and effects - Brandsen, Taco; Trommel, Willem Adriaan; Verschuere, Bram (Governance and public mangement series, 2014)
"Faced with declining social cohesion, more and more governments are trying to revitalise society by attempting to reconstruct local communities, civil society and citizenship. One way to do this is to share public responsibilities with organized citizens and third sector organisations. As a result, relationships with citizens, communities and third sector organisations are increasingly brought within the realm of public management, subject to accountability procedures, embedded in hierarchical structures, included in arenas for competition and contracting. This volume examines the emergence of this new type of governance, exploring the dynamics, effectiveness and appropriateness of this governmental response to the fragmentation of modern social life. "--